SCREENING OF WHEAT GENOTYPES FOR WATER DEFICIT CONDITIONS UNDER THE SCENARIO OF CLIMATE CHANGE - SARWAR, MA; YAR, US; AMIN, HAB; MUNIR, T; IQBAL, HI; AHSAN, MT; UMAR, F; RABNAWAZ, .; HUSSAIN, MI; ALI, S; et al. (Biological and Clinical Sciences Research Journal, 2024)
The top-ranked crop in cereals, wheat feeds people around the globe more than any other food crop, with a diversity of uses in the food industry. The global production of wheat is 250 million tons which is still not enough to address the needs of the ever-increasing human population. Wheat plays a vital role in the human diet because it is the source of protein, carbohydrates, and calories. Due to its wider adaptation wheat is sown as a rain-fed and irrigated crop. Drought upsets the crop during all growth and developmental stages and all these stages of the crop are not equally affected by the drought. At initial growth stages, water stress reduces plant emergence and germination and causes a reduction in plant growth by reducing its height, number of productive tillers, and total leaf surface area. When drought occurs at anthesis it reduces the percentage of fertile spikelets. This research aimed to check the response of wheat genotypes under drought stress for different morphological attributes at the maturity stage. Significant results were obtained under drought and normal conditions. The data were further analyzed under PCA for the selection of best genotypes under normal and stress conditions. Zincol performed well under both conditions. Results obtained from this research will be useful in selecting the best genotypes for rainfed and water-stress environments in future breeding programs.